2002
DOI: 10.2172/15010050
|View full text |Cite
|
Sign up to set email alerts
|

Hanford Site Environmental Report for Calendar Year 2001

Abstract: This report was prepared as an account of work sponsored by an agency of the United States Government. Reference herein to any specific commercial product, process, or service by trade name, trademark, manufacturer, or otherwise does not necessarily constitute or imply its endorsement, recommendation, or favoring by the United States Government or any agency thereof, or Battelle Memorial Institute. This report is a summary of major or significant activities occurring at the Hanford Site only, and is not a full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…At the 300 Area's southern border, a cross-river water sampling transect found that all water samples were below ambient surface water quality criteria and that slightly elevated (compared to both mid-river) concentrations of anions and total uranium were found for the Franklin County shore. The slightly elevated concentrations of anions and total uranium along the Franklin County shoreline has been observed in prior sampling efforts and likely resulted from extensive irrigation in the area (Poston et al 2001;Poston et al 2002).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…At the 300 Area's southern border, a cross-river water sampling transect found that all water samples were below ambient surface water quality criteria and that slightly elevated (compared to both mid-river) concentrations of anions and total uranium were found for the Franklin County shore. The slightly elevated concentrations of anions and total uranium along the Franklin County shoreline has been observed in prior sampling efforts and likely resulted from extensive irrigation in the area (Poston et al 2001;Poston et al 2002).…”
Section: Discussionmentioning
confidence: 74%
“…It was not possible to collect all samples on the same day because of the large study area, numerous target biota, and the large amount of samples required. Water sampling dates (all in 2001) and daily (24-hour) average flow conditions for the Columbia River measured at Priest Rapids Dam (Poston et al 2002) are discussed below. The 300 Area and Vernita Bridge river water and 300 Area riverbank spring water was collected on August 27 at 2,680 cubic meters (95,700 cubic feet) per second river flow.…”
Section: Sample Collection and Analysis Methodsmentioning
confidence: 99%
“…Because disposed and discharged quantities of fission products could be related to the production of special nuclear materials, early records were secret and few efforts were made to develop or show total inventories of radionuclides with greater impact to man and the environment (e.g., technetium-99, iodine-129) until very near the end of Hanford's production mission. Our knowledge of the presence, abundance, and health implications of some radionuclides also Primary Source (b) Tritium (c) Groundwater monitoring (Hartman et al 2003) Carbon-14 Carbon-14 Groundwater monitoring (Hartman et al 2003); Air monitoring (Poston et al 2002) Chlorine-36 1998 Composite Analysis (Kincaid et al 1998), SPRD EIS (DOE 1989) Selenium-79 Immobilized Low-Activity Waste (ILAW) Performance Assessment (DOE 2001) Strontium-90 (c) Groundwater monitoring (Hartman et al 2003) Technetium-99 Groundwater monitoring (Hartman et al 2003) Iodine-129 Iodine-129…”
Section: Major Data Sourcesmentioning
confidence: 99%
“…Cesium-137 Groundwater monitoring (Hartman et al 2003) Europium-152 Surface water monitoring (Poston et al 2002) Radium-226 (d) ERDF RI/FS (DOE 1994) Protactinium-231 Groundwater monitoring (Hartman et al 2003) Uranium-235 (c) Groundwater monitoring (Hartman et al 2003) Neptunium-237 ILAW Performance Assessment (DOE 2001) Uranium-238 (c) Groundwater monitoring (Hartman et al 2003) (a) Atmospheric monitoring does not identify any radionuclides at or near the standard, and, therefore, fails to identify any radionuclides requiring inclusion in Hanford assessments. Carbon-14 is included as an atmospheric radioactive contaminant of potential concern in Hanford assessments because it appears in the surplus production reactor environmental impact statement (DOE 1989) as an atmospheric radioactive contaminant of concern.…”
Section: Major Data Sourcesmentioning
confidence: 99%
“…Hexavalent chromium is a contaminant of concern for the Hanford Site because of its use as a corrosion inhibitor for cooling water systems in the nuclear reactors. Direct discharges of chromium to the river ended with the shutdown of the last single-pass reactor in 1971; however, residual chromium is still present in the soil column, groundwater, and some biota (Poston et al 2002.…”
Section: Introductionmentioning
confidence: 99%